How a Firm’s Competitive Environment and Digital Strategic Posture Influence Digital Business Strategy1 - Mithas, Sunil; Tafti, Ali; Mitchell, Will (MIS Quarterly, 2013)
In this paper, we examine how the competitive industry environment shapes the way that digital strategic posture (defined as a focal firm’s degree of engagement in a particular class of digital business practices relative to the industry norm) influences firms’ realized digital business strategy. We focus on two forms of digital strategy: general IT investment and IT outsourcing investment. Drawing from prior literature on determinants of IT activity and competitive dynamics, we argue that three elements of the industry environment determine whether digital strategic posture has an increasingly convergent or divergent influence on digital business strategy. By divergent influence, we mean an influence that leads to spending substantially more or less on a particular strategic activity than industry norms. We predict that a digital strategic posture (difference from the industry mean) has an increasingly divergent effect on digital business strategy under higher industry turbulence, while having an increasingly convergent effect on digital business strategy under higher industry concentration and higher industry growth. The study uses archival data for 400 U.S.-based firms from 1999 to 2006. Our findings imply that digital business strategy is not solely a matter of optimizing firm operations internally or of responding to one or two focal competitors, but also arises strikingly from awareness and responsiveness to the digital business competitive environment. Collectively, the findings provide insights on how strategic posture and industry environment influence firms’ digital business strategy.